Puntius kamalika, a new species of barb from Sri Lanka (Teleostei: Cyprinidae) - Silva, Anjana; Maduwage, Kalana; Pethiyagoda, Rohan (Zootaxa, 2008)
Since its first record from the island in 1912, the barb Puntius amphibius Valenciennes has regularly featured in Sri Lanka’s ichthyofaunal inventories. Recent work has shown, however, that the name P. amphibius should be reserved for a species originally collected from Bombay, India, and described by Achille Valenciennes in 1842, now known only from its lectotype. The Sri Lankan fish hitherto known by this name is an undescribed species. Puntius kamalika, new species, is distinguished from all Sri Lankan and peninsular-Indian congeners by having (in addition to a suite of mensural characters) ½4/1/2½ scales in transverse line between mid-dorsal scale row and pelvic-fin origin and lacking any prominent markings on fins and body in both living and preserved examples. The new species is widely distributed in the island’s wet-zone lowlands (rainfall > 2,500 mm yr -1 ), where it occurs in streams, rivers and marshes between the Kelani-River basin draining to the island’s west, and the Gin River basin to the south. It is locally common.